Analisis Analisis Faktor yang Berhubungan dengan Penerimaan Masyarakat terhadap Vaksin Corona Virus Disease 19 (Covid-19) - Dina Dama Yanti; Tri - Anjaswarni; Tri Nataliswati; Sumirah Budi Pertami (Poltekkes Kemenkes Malang, 2024)
Abstract: Corona Virus 2019 (Covid 19) is an acute respiratory infection and can cause death due to acute pneumonia. One of the efforts to prevent Covid-19 is vaccination. Covid-19 vaccination is the government's effort to provide antigens to the human body so that the body's immunity increases and is immune to attacks by the Corona virus. The aim of the research is to analyze the relationship between education, knowledge, availability of information and family support with acceptance of Covid-19 vaccination. Type of correlational research with Cross Sectional design. The sampling technique was simple random sampling of 77 respondents. The instrument uses a questionnaire developed by the researcher himself to measure the independent variables: knowledge factors, education, availability of information, family support and the dependent variable: acceptance of the Covid-19 vaccine. The analysis uses the Chi Square test to analysis factors related to community acceptance of the Covid-19 vaccine. The research results show that there is a significant relationship between education, knowledge, availability of information and family support with community acceptance of the Covid-19 vaccine with a p-value < ? (0.05). The p-value of education 0.039, knowledge 0.023, availability of information 0.013 and family support 0.005. These results are quite reasonable because knowledge, education, information and family support can strengthen an individual's attitude in making decisions and providing a positive perception of a policy. Recommendation: Continuous provision of information and support is important so that people have a positive attitude and support the Covid-19 vaccine policy. Keywords: Factors, Community Acceptance, Covid-19 Vaccine Abstrak: Coronavirus 2019 (Covid 19) adalah penyakit infeksi pernafasan akut yang dapat menyebabkan kematian akibat pneumonia akut. Salah satu upaya pencegahan covid-19 adalah vaksinasi. Vaksinasi Covid-19 merupakan upaya pemerintah dengan memberikan antigen pada tubuh manusia agar imunitas tubuh meningkat dan kebal terhadap serangan virus Corona. Tujuan penelitian adalah menganalisis hubungan pendidikan, pengetahuan, ketersediaan informasi dan dukungan keluarga dengan penerimaan vaksinasi Covid-19. Jenis penelitian korelational dengan desain Cross Sectional. Teknik pengambilan sampel dengan simple random sampling sejumlah 77 responden. Instrumen menggunakan kuesioner yang dikembangkan sendiri oleh peneliti untuk mengukur variabel bebas: faktor pengetahuan, pendidikan, ketersediaan informasi, dukungan keluarga dan variabel terikat: penerimaan vaksin covid-19. Analisis menggunakan uji Chi Square untuk mengetahui faktor yang berhubungan dengan penerimaan masyarakat terhadap vaksin Covid-19. Hasil penelitian ada hubungan signifikan antara pendidikan, pengetahuan, ketersediaan informasi, dan dukungan keluarga dengan penerimaan masyarakat terhadap vaksin covid-19 dengan p-value < ?(0,05). Nilai pv pendidikan 0,039, pengetahuan 0,023, ketersediaan informasi 0,013 dan dukungan keluarga 0,005. Hasil ini cukup beralasan karena pengetahuan, pendidikan, informasi dan dukungan keluarga, dapat memperkuat sikap individu dalam membuat keputusan dan memberikan penilaian yang positif terhadap suatu kebijakan. Rekomendasi: pemberian informasi dan dukungan secara terus menerus penting dilakukan agar masyarakat mempunyai sikap yang positif dan mendukung kebijakan vaksin covid-19. Kata kunci: Faktor, Penerimaan Masyarakat, Vaksin Covid-19